Trends of Physical Education Teachers' Motivation in Performing Teaching Assignments - Indrayogi Indrayogi; Davi Sofyan (Universitas Majalengka, 2023)
Education has an important role in improving the quality of human resources in Indonesia. This educational activity must be carried out continuously in order to produce quality human beings and have reliable abilities in order to face increasingly fierce competition in the future. The aim of the research is to find out the teacher's motivation which has not been maximized, especially in terms of student learning at the elementary school education level, which is suspected to still not meet good service and quality standards. The method used is descriptive method with a quantitative approach, the population in this study were physical education teachers in Sukahaji District, Majalengka Regency, totaling 25 people. The sample used in this study was physical education teachers who had an undergraduate degree totaling 15 teachers. From the results of data analysis, it was found that the physical education teacher's motivation variable was 79.1333 with a standard deviation of 9.97043. The teaching ability variable obtained a mean of 69.000 with a standard deviation of 7.54037. The regression equation line Y = 15.779 +0.673. These results indicate that it can be interpreted that if the motivation of physical education teachers is good or increases, their teaching abilities will be good or increase as well